Enhancing Entrepreneurial Skills Through Geographic Information Systems (GIS) in Technology Education: A Study of Nigerian Secondary Schools - Nwoye, Theresa Nwakaego (Pusmedia Group Indonesia, 2024)
Lack of integration of geographic information systems (GIS) in technology education in Nigerian secondary schools, resulting in gaps in students’ practical skills development for entrepreneurship. This is compounded by inadequate curriculum support for technology-based entrepreneurship education, leaving students unprepared for real-world business challenges. The objective of the study was to investigated the integration of Geographic Information Systems (GIS) in technology education to enhance entrepreneurial skills among secondary school students in Anambra State, Nigeria. The study utilized a descriptive research design targeting 141 technology education teachers across secondary schools. A multistage sampling technique ensured diverse participation. Data were collected via a validated structured questionnaire assessing GIS awareness and challenges. Data were analyzed using SPSS. Findings revealed that teachers generally lacked awareness and training in GIS applications, which limited effective integration into the curriculum. The study identified challenges such as limited access to GIS software, inadequate institutional support, high costs of GIS tools, and resistance to new technologies. Despite these challenges, the potential of GIS to foster critical thinking, collaboration, and data-driven decision-making was recognized. The study concluded that enhancing GIS integration in technology education could significantly improve entrepreneurial skills among students, recommending targeted training for teachers and improved resource allocation to facilitate GIS adoption